SEROPREVALENCE OF BRUCELLA SP. IN CATTLE OF TARMA DISTRICT, JUNÍN-PERU - Ventocilla G., Sandra (2009)
The objective of this study was to determine the presence of Brucella sp. in cattle of the district of Tarma, Junin-Peru. Blood samples of 344 cows were collected for detection of antibodies against Brucella sp. by Rose Bengal Plate test. None of the samples tested resulted positive to antibodies against Brucella sp. The results suggest the absence of the bacteria or that the prevalence is less than 1% in the evaluated population. The results might be used for the Peruvian National Service of Animal Health to establish an epidemiological surveillance programme for maintaining the area “free” of the disease.